Incidence, locations, and longitudinal course of cerebral microbleeds in european moyamoya - Wenz, Holger; Maros, Máté E.; Ehrlich, Gregory Marius; Al-Zghloul, Mansour; Groden, Christoph; Förster, Alex (Stroke, 2017)
Background and Purpose—Cerebral microbleeds (cMBs) have previously been linked with especially high incidence in Asian patients with moyamoya together with high tendency to bleed. This, presumably, is characteristic of patients with moyamoya. Herein, we, therefore, investigate retrospectively the frequency, location, and longitudinal course of cMBs in a large German cohort.Methods—We included all patients with moyamoya who underwent standard magnetic resonance imaging, including T2*-weighted images, in our department between 1998 and 2015. Two independent readers evaluated magnetic resonance imaging scans to determine the occurrence of cMBs according to the Brain Observer Microbleed Scale. Demographics, initial symptoms leading to hospitalization, and associated diseases were obtained by chart review.Results—Overall, there was a total of 242 T2* studies of 101 included moyamoya patients available with a strong female predominance (69.3%). Eight patients (7.9%) were ≤18 years of age. We detected 25 cMBs within 13 patients (12.9%). One patient <18 of age was presented with a cMB; 2 of 3 patients with an intracranial hemorrhage as initial event demonstrated cMB(s). In 72 of 101 cases, there were 1719 person months of follow-up, with 3 adult patients showing 3 de novo cMBs in the course. The majority of cMBs (64.0%) were located at the cortex/gray-white junction.Conclusions—Although the frequency of cMBs herein is much higher than the expected age-specific incidence, it is still much lower compared with previous reports on cMBs in moyamoya patients of Asian descent. These results might reflect another ethnic-specific difference in patients diagnosed with moyamoya.